Perancangan Video Pariwisata Kawah Wurung Bondowoso Sebagai Media Promosi - Dwi Cahyaningtyas Mulyani; Pujiyanto Pujiyanto; Rina Nurfitri (LPPM STIKI Malang, 2020)
Bondowoso is one of the regencies in Indonesia that has potential, including its natural tourism potential. Bondowoso is the only district in the â€œTapal Kudaâ€ area that does not have a coastline. Many potential tourism objects owned by Bondowoso Regency, one of which is